The Gray Zone: Adolescent and Young Adult Decision Support Needs for Ulcerative Colitis. Issue 2 (July 2020) - Meisman, Andrea; Daraiseh, Nancy M.; Minar, Phil; Saxe, Marlee; Lipstein, Ellen A.
Purpose. To understand the medical decision support needs specific to adolescents and young adults (AYAs) with ulcerative colitis (UC) and inform development of a decision support tool addressing AYAs' preferences.Methods. We conducted focus groups with AYAs with UC and mentors from a pediatric inflammatory bowel disease clinic's peer mentoring program. Focus groups were led by a single trained facilitator using a semistructured guide aimed at eliciting AYAs' roles in medical decision making and perceived decision support needs. All focus groups were audio recorded, transcribed, and coded by the research team. Data were analyzed using content analysis and the immersion crystallization method.Results. The facilitator led six focus groups: one group with peer mentors aged 18 to 24 years, three groups with patients aged 14 to 17 years, and two groups with patients aged 18 to 24 years. Decision timing and those involved in decision making were identified as interacting components of treatment decision making. Treatment decisions by AYAs were further based on timing, location (inpatient v. outpatient), and family preference for making decisions during or outside of clinic. AYAs involved parents and health care providers in medical decisions, with older participants describing themselves as "final decision makers." Knowledge and experience were facilitators identified to participating in medical decision making.Conclusions. AYAs with UC experience changes to their roles in medical decisions over time. The support needs identified will inform the development of strategies, such as decision support tools, to help AYAs with chronic conditions develop and use skills needed for participating in medical decision making.